Proposal for Ichnotaxonomic Allocation of Therapsid Footprints from the Botucatu Formation (Brazil) - D'Orazi Porchetti, Simone; Bertini, Reinaldo J. [UNESP]; Langer, Max C. (Taylor & Francis, 2018)
A new ichnospecies, Brasilichnium anaiti, is erected on material from the Botucatu Formation of Brazil. The general morphology supports ichnotaxonomic similarity between the new ichnotaxon and Brasilichnium elusivum Leonardi, 1981, even if a separation at the ichnospecies level is evident, based on differences in shape and arrangement of pes digit marks along with a clear dimensional gap between both ichnotaxa. Similar forms from the Lower Jurassic of the United States are known and should be included under this new ichnotaxonomic label, based on shared morphological features. B. anaiti is constantly associated with B. elusivum in dune foresets of hyperarid paleoenvironments, to which these forms are restricted. This makes B. anaiti a further element of the Brasilichnium ichnocoenosis in the larger framework of the Chelichnus ichnofacies. Re–evaluation of possible trackmakers highlights the difficulties of unequivocal referring this ichnotaxon to a specific producer, but restrains potential trackmakers to early mammaliamorph therapsids.
Keywords: Botucatu Formation; Brasilichnium anaiti; Brazil; Mammaliamorph therapsids; Paleoerg